Rosiglitazone Exerts an Anti-depressive Effect in Unpredictable Chronic Mild-Stress-Induced Depressive Mice by Maintaining Essential Neuron Autophagy and Inhibiting Excessive Astrocytic Apoptosis - Zhao, Zhan; Zhang, Ling; Guo, Xu-Dong; Cao, Lu-Lu; Xue, Teng-Fei; Zhao, Xiao-Jie; Yang, Dan-Dan; Yang, Jin; Ji, Juan; Huang, Ji-Ye; Sun, Xiu-Lan (Frontiers in Molecular Neuroscience, 2017)
There is increasing interest in the association between depression and the development of metabolic diseases. Rosiglitazone, a therapeutic drug used to treat type 2 diabetes mellitus, has shown neuroprotective effects in patients with stroke and Alzheimer’s disease. The present study was performed to evaluate the possible roles of rosiglitazone in in vivo (unpredictable chronic mild stress-induced depressive mouse model) and in vitro (corticosterone-induced cellular model) depressive models. The results showed that rosiglitazone reversed depressive behaviors in mice, as indicated by the forced swimming test and open field test. Rosiglitazone was also found to inhibit the inflammatory response, decrease corticosterone levels, and promote astrocyte proliferation and neuronal axon plasticity in the prefrontal cortex of mice. This series of in vivo and in vitro experiments showed that autophagy among neurons was inhibited in depressive models and that rosiglitazone promoted autophagy by upregulating LKB1, which exerted neuroprotective effects. Rosiglitazone was also found to activate the Akt/CREB pathway by increasing IGF-1R expression and IGF-1 protein levels, thereby playing an anti-apoptotic role in astrocytes. Rosiglitazone’s autophagy promotion and neuroprotective effects were found to be reversed by the PPARγ antagonist T0070907 in primary neurons and by PPARγ knockdown in an N2a cell line. In conclusion, we found that rosiglitazone protects both neurons and astrocytes in in vivo and in vitro depressive models, thereby playing an anti-depressive role. These findings suggest that PPARγ could be a new target in the development of anti-depressive drugs.